Komunikasi Persuasif Mamak Terhadap Kemanakan Dalam Penerapan Falsafah Kato Nan Ampek Di Nagori Koto Panjang - Doni Muliadi; Syafwan Rozi (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2024)
Thesis on behalf of Doni Muliadi, NIM : 4318081, This thesis is entitled "Mamak's Persuasive Communication Against His Cousins ​​in the Application of Kato Nan Ampek's Philosophy in Nagori Koto Panjang. Student of Islamic Communication and Broadcasting Study Program, Faculty of Ushuluddin Adab and Da'wah. This study proposes two main issues, namely how the factors influence, the Forms of Mamak's Persuasive Communication Against Childhood in the Application of Kato Nan Ampek's Philosophy in Nagori Koto Panjang. The research method used is qualitative which is descriptive qualitative, with the aim of being able to describe the phenomenon of society in maintaining Mamak's communication with Kemanakan. The results of this study can be concluded that the factors that influence Mamak's Persuasive Communication regarding whereabouts are clarity of purpose, things that pay attention to the person who is the other person talking to, and the right way to invite friends to apply the Kato Nan Ampek Philosophy in Nagori Koto Panjang so that there is communication between mamak and whereabouts. Forms of Mamak's Persuasive Communication towards Kemanakan by inviting whereabouts to use persuasive words, kind words towards nephews with the aim of giving an impression that can be interesting to Kemanakans to apply polite words and repeat them, giving rewards for what is done whereabouts by giving good or bad threats and embracing events that attract public attention in the form of violations of customary norms which are often found by speaking harshly to other people so that the existence of Mamak's Persuasive Communication towards Kemanakan can change the application of the Kato nan Ampek Philosophy in Nagori Koto Panjang.